CLINICO-STATISTICAL STUDIES REGARDING THE FREQUENCY OF SUPERNUMERARY TEETH IN A GROUP OF CHILDREN IN TG. MURES - Mariana Pacurar; Emanuela Tegla; Claudiu Vartolomei; Ana Petra Lazar; Dan Serbanoiu; Silvia Pop; Manuela Chibelean; Cristina Pollman (Amaltea Medical Publishing House, 2018)
Supernumerary teeth represent a maxillarry dental anomaly of number, registered in the 1st Angle class. The goal of the authors was to analyze the frequency and the pattern of these anomalies in number in a group of patients who presented for an orthodontic treatment at the Clinic of Orthodontics and Pediatric Dentistry of the Faculty of Dentistry, UMFST Tg. Mures between the years 2015 and 2018 and to establish correlations between this anomaly and other pathologies belonging to the orthodontic field. The analyzed variables included age, gender, health condition, constitution, origin, and the statistical analysis was focused on the following parameters: the affected dentition and arch sector, number of supernumerary teeth and their location, association with other anomalies, onset of complications.